Quality of Follow-up: Systematic Review of the Research in Bariatric Surgery. Issue 5 (May 2016) - Switzer, Noah J.; Merani, Shaheed; Skubleny, Daniel; Pelletier, Jean-Sébastien; Kanji, Raisa; Shi, Xinzhe; Birch, Daniel W.; de Gara, Christopher; Sharma, Arya M.; Gill, Richdeep S.; Karmali, Shahzeer
Abstract : Objective: We aim to systematically review the bariatric surgery literature with regards to adequacy of patient follow-up, meeting the McMaster criteria of ≥80% follow-up. Background: Loss to follow-up is a major concern and can potentially bias the outcome and interpretation of a study. The quality of follow-up in bariatric surgery is quite variable with recent systematic reviews criticizing the field for its lack of overall follow-up. Methods: A complete search of PubMed was performed. Literature was restricted to a range of 5 years (2007–2012), English language, and publications listed in PubMed. The McMaster Evidence-based Criteria for High Quality Studies was used to assess the follow-up data adequacy and a logistic meta-regression was performed to identify factors associated with high quality follow-up studies. Results: Ninety-nine published manuscripts were included. For follow-up at study end, only 40/99 (40.4%) of papers had adequate patient follow-up, 42/99 (42.4%) failed to meet the McMaster criteria and 17/99 (17.2%) failed to report any follow-up results. On average, 31% were lost to follow-up at the study's end. Only shorter study duration, and if the study was performed in the US, were associated with studies meeting the McMaster criteria. Conclusions: Only 40% of studies in the bariatric surgery literature meet criteria for adequate follow-up. On average, studies have 30% of patients lost to follow-up at the stated end-point. Identified study characteristics associated with high quality follow-up included shorter study duration and studies performed in the US.